Teaching mathematics for social justice : conversations with educators - Wager, Anita A.; Stinson, David W. (Reston, VA : National Council of Teachers of Mathematics, 2012)
"This collection of original articles is the start of a compelling conversation among some of the leading figures in critical and social justice mathematics, a number of teachers and educators who have been inspired by them-and who have inspiring stories of their own to tell - and any reader interested in the intersection of education and social justice. An important read for every educator, this book shows how to teach mathematics so that all students are given the tools they need to confront issues of social justice today and in the years ahead"--page [4] of cover.
pt. III : Teacher education and professional development. Beyond apples, puppy dogs, and ice cream : preparing teachers to teach mathematics for equity and social justice / Courtney Koestler -- Challenging beliefs and dispositions : learning to teach mathematics for social justice / Jacqueline Leonard, Brian R. Evans -- Is this teaching mathematics for social justice? Teachers' conceptions of mathematics classrooms for social justice / Tonya Gau Bartell -- Valuing the process : working with teachers around mathematics for social justice / Lidia Gonzalez -- pt. IV : Teaching mathematics for social justice in the classroom. Numbers count : mathematics across the curriculum / Bob Peterson -- Toys for boys? Challenging domestic violence using mathematics / David Stocker -- Five things you should probably know about teaching mathematics for social justice / John O. Wamsted -- Teaching mathematics for social justice : the end of "when are we ever going to use this?" / Ginny C. Powell -- pt. V : Conclusion. A broad concept of social justice / Ubiratan D'Ambrosio.
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching; Social justice; Mathematics teachers -- In-service training; Mathematics -- Study and teaching; Mathematics teachers -- In-service training; Social justice